Lateralization of memory function in temporal lobe epilepsy using scene memory fMRI - William S. Tackett; Dawn Mechanic‐Hamilton; Sandhitsu Das; Marissa Mojena; Joel M. Stein; Kathryn A. Davis; John A. Detre (Epilepsia Open)
Abstract Functional magnetic resonance imaging (fMRI) offers an alternative to the traditional Wada test for presurgical language and memory lateralization that carries almost no risk. However, fMRI lateralization of episodic memory remains challenging because the hippocampus, which is fundamental to episodic memory, is smaller, more prone to susceptibility artifact, and harder to functionally modulate than language regions. We previously showed that a complex scene memory task can lateralize memory function in the mesial temporal lobe. Using data acquired from N = 45 patients with temporal lobe epilepsy acquired with an improved stimulus paradigm and high‐resolution fMRI, we now demonstrate that memory activation can be successfully lateralized within hippocampus proper. Plain Language Summary Epilepsy surgery can improve seizure control in patients with temporal lobe epilepsy (TLE) that cannot be controlled with medications also, but ablation or removal of temporal lobe brain tissue can also cause cognitive deficits. Functional MRI (fMRI) can noninvasively map brain activation and perform well in lateralizing and localizing language function, but localizing and lateralizing memory function is more challenging. Building upon prior work using complex scene encoding to map memory function, we demonstrate that the use of high‐resolution fMRI along with an optimized task paradigm allows memory activation to be detected within the hippocampus. Because the hippocampus is both a common site of TLE and a key region underlying memory, this approach is expected to contribute to presurgical evaluation of TLE.